Reduced serum sestrin 2 levels in Hashimoto’s disease: a cross-sectional study on a potential pathophysiological and diagnostic role - Merve Ates; Mesut Ates; Murat Alisik; Ozgur Mehmet Yis (Endocrine Connections, 2025)
Objective: Expression of mammalian target of rapamycin (mTOR), which plays a key role in coordinating the balance between cell growth and autophagy, is elevated in thyroid tissues of patients with Hashimoto’s disease. Sestrins are an evolutionarily conserved, stress-inducible protein family that reduces oxidative stress and regulates the adenosine monophosphate-dependent protein kinase (AMPK)-mTOR signaling pathway. The aim of this study was to investigate the potential role and significance of sestrin 2 (SESN2), a member of the sestrin family, in Hashimoto’s disease. Methods: This cross-sectional study included patients with Hashimoto’s disease and healthy volunteers. Thyroid autoantibodies, free T4, TSH, and sestrin 2 were measured from blood samples. Sestrin 2 was analyzed by an ELISA kit.Results: One hundred ten patients and 64 healthy volunteers were included in the study. Median SESN2 levels in the patient group (1.36 ng/mL (1.10–2.03)) were significantly lower than in the control group (1.83 ng/mL (1.34–2.64)) (P = 0.002). There was no significant difference in SESN2 levels between euthyroid and subclinical hypothyroidism subgroups of patients (P > 0.05). Conclusion: In this study, serum SESN2 levels were found to be lower in patients with Hashimoto’s disease than in healthy adults, suggesting that SESN2 may have a role in the pathophysiology of Hashimoto’s disease. These results indicate that further research is needed to better understand the effect of regulation of SESN2 in Hashimoto’s disease on the course and pathological processes of the disease.